2022
DOI: 10.3390/vaccines10050649
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Immunogenicity of Three Different Homo- and Heterologous Vaccination Regimens against SARS-CoV-2

Abstract: Background: Due to findings on adverse reactions and clinical efficacy of different vaccinations against SARS-CoV-2, the administration of vaccination regimens containing both adenoviral vector vaccines and mRNA-based vaccines has become common. Data are still needed on the direct comparison of immunogenicity for these different regimens. Methods: We compared markers for immunogenicity (anti-S1 IgG/IgA, neutralizing antibodies, and T-cell response) with three different vaccination regimens (homologous ChAdOx1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…The homologous vaccine regimen with ChAdOx resulted in a higher risk of being below the given threshold. This finding is in accordance with recent studies where this vaccine regimen led to a weaker immune response, whereas BNT162b2/BNT162b2 vaccines elicit a stronger antibody response [ 31 , 32 ]. Studies also showed that heterologous vaccines regimen mostly ChAdOx/BNT162b2 tend to have a stronger immunogenicity than homologous BNT162b2 regimen because of the additional effect of each vaccine on the humoral immune system response [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The homologous vaccine regimen with ChAdOx resulted in a higher risk of being below the given threshold. This finding is in accordance with recent studies where this vaccine regimen led to a weaker immune response, whereas BNT162b2/BNT162b2 vaccines elicit a stronger antibody response [ 31 , 32 ]. Studies also showed that heterologous vaccines regimen mostly ChAdOx/BNT162b2 tend to have a stronger immunogenicity than homologous BNT162b2 regimen because of the additional effect of each vaccine on the humoral immune system response [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we saw that each administered vaccinations reduced the risk of being below the threshold. Time since vaccination is a widely known risk factor for waning antibodies levels [ 30 , 31 ], which was also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, others found anti-S1 IgG positivity in only 75.0–77.4% (Chile) [ 16 , 24 ]. The relevance of the second vaccine dose for eliciting markedly increased antibody titers has also been established for other COVID-19 vaccination regimens [ 25 , 26 , 27 ]. Compared to CoronaVac, both vector- and mRNA-based vaccines (e.g., ChAdOx1 and BNT162b2) elicit much higher anti-S1 titers and positivity rates already after the first vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
“…There were two strategies for using the booster dose vaccine: homologous (using the same vaccine platform) and heterologous (using a different vaccine platform) when compared to the previous two doses of the vaccination. Several studies have found that heterologous vaccines outperform homologous vaccines in terms of higher antibody production and T-cell activation in both the general population and KTRs [ 22 , 23 , 38 ]. The rate of seroconversion can be achieved in 60–70% of primary non-responders with a heterologous booster dose, leaving 20–25% of KTRs with no seroconversion after receiving a booster dose [ 15 , 16 , 39 ].…”
Section: Discussionmentioning
confidence: 99%